Comparative Analysis of Added Value of Green Bean and Roast Bean in Bener Meriah Regency, North Sumatra Province, Indonesia - Satia Negara Lubis; M. Jufri (Agro Bali : Agricultural Journal, 2022)
This study aims to determine the amount of added value in the processing of coffee beans (Green bean) and coffee roast beans in Keramat Jaya Village, Bandar District, Bener Meriah Regency per one process. Methods The determination of the sample in this study, namely arabica coffee farmers who process logs of coffee (Cherry red) into coffee beans (Green bean) totaling 12 farmers will be sampled. Meanwhile, Green Bean coffee processors will be determined by the snowball sampling method. The results of this study indicate that the added value in the business of processing coffee logs (Cherry Red) into coffee beans (Green beans) has an added value ratio of 29.7%. The added value in the business of processing green beans into Roast Bean coffee has an added value ratio of 38.17%.